The Future of Knowledge, and the Fate of Wisdom, in the Age of Information - Lance Strate (Philosophies)
John Henry Newman defined the university as “a place of teaching universal knowledge”, which suggests that it is also an environment for the teaching and creation of knowledge, and therefore a medium for the teaching and creation of knowledge. Based on the field of media ecology, defined by Neil Postman as “the study of media as environments”, and following Marshall McLuhan’s famous maxim that, “the medium is the message”, we can understand knowledge to be the product of a particular type of medium or environment. Taking inspiration from the poetic questions posed by T.S. Eliot, “Where is the wisdom we have lost in knowledge? Where is the knowledge we have lost in information?”, this essay takes issue with the view expressed among internet boosters that information is the basis of knowledge, and knowledge is the basis of wisdom. Instead, an alternative understanding presented in which information as a contemporary phenomenon is a product of the electronic media environment, knowledge is a product of the literacy associated with the chirographic and typographic media environments, and wisdom is a product of the oral media environment.